Отбор проб и анализ природных газов нефтегазоносных бассейнов - Ванюшин В. А. Виталий Анатольевич; Завьялова Л. М. Лидия Михайловна; Коробейник Г. С. Галина Сергеевна; Корценштейн В. Н.; Кушниров В. В.; Старобинец И. С. Илья Самойлович; Калинко М. К. (Москва, Недра, 1985)
Авт. указаны на обороте тит. л.